ANALISISINTENSITAS PENGGUNAANGADGETDAN PEMANFAATANINTERNETTERHADAP MOTIVASI BELAJAR - Meyta Pritandhari (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
Learning is a process which can determine the success of learning. The process of learning done over and over again in the same way and method will lead to boredom in learning. In this globalization era, learning can be done anywhere, anytime and in many ways. One of the most popular learning methods is using gadgets. Gadgets can help us in overcoming problems encountered. Utilization of a positive gadget will bring good impact for its users. And conversely, if the use of gadgets that are negative and excessive will bring adverse effects to its users.The intensity of gadget and internet usage has a positive impact in students' learning motivation. Students can take advantage of gadgets and internet in searching for broader references related to learning. They are more interested in learning to use gadgetsand the internet than by just using books. It is not denied that gadgets and the internet have a negative impact if the user can not wisely use it. However, the use of gadgets and the internet can be directed to students in order to utilize both positively.